Pengaruh Promosi Dan Harga Terhadap Minat Beli Konsumen Pada Jasa Fotografi Dan Videografi Whitetalk Picture Di Bogor - Abdurahim, Adedi; Septiani, Fauziah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to find out how promotion and price influence consumer purchasing interest in Whitetalk Picture photography and videography services in Bogor, both partially and simultaneously. This research method uses quantitative methods with a sample size of 145 respondents. The data collection technique is by means of a questionnaire, and the data analysis techniques are validity test, reliability test, simple linear analysis, multiple linear analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results of this research show that there is a significant influence between Promotion and Price on Consumer Purchase Interest simultaneously. This can be seen from the value of the multiple linear regression equation, namely Y = 16,719 + 0,147 X1 + 0,444 X2. A constant of 16,719 indicates that if there is a change in the constant of the independent variable (X1) and The multiple correlation coefficient value shows that the Promotion (X1) and Price (X2) variables have a significant influence on Consumer Purchase Interest (Y), with a significant change value in F of 0.000 or less than 0.05, the correlation coefficient value is 0,583 and is positive. Where this value is in the interval 0,400 – 0,599, it means that the two variables have a moderate effect level of relationship. The Determination Coefficient value is 0,340, so it can be concluded that the Promotion (X1) and Price (X2) variables influence the Consumer Purchase Interest variable (Y) by 34.0% while the remaining 66.0% is influenced by other factors. Simultaneously testing the hypothesis obtained a calculated F value > F table or (42.453 > 3.05), this was also strengthened by a ρ value < Sig.0.05 or (0.000 < 0.05). This shows that there is a significant simultaneous influence between Promotion and Price on Consumer Purchase Interest in Whitetalk Picture Photography and Videography Services in Bogor.